An anionic and cationic surfactant-assisted hydrothermal synthesis of cobalt oxide nanoparticles as the active electrode material for supercapacitors. (27th January 2021) - Samal, R. R.; Samantara, Aneeya K.; Mahalik, S.; Behera, J. N.; Dash, B.; Sanjay, K.
Abstract : Schematic representation of surfactant action for synthesis of cobalt hydroxide and oxide. Abstract : The depletion of the traditional fuels and unavoidable seasonal intermittence in solar/wind energy has made an urgent call to develop suitable energy conversion and storage systems. Since both the efficiency and cost of these systems are greatly impacted by electroactive materials, designing an efficient material through a scalable methodology is indispensable. Keeping these things in mind, we demonstrated the synthesis of Co3 O4 nanoflakes via the anionic (cetyl trimethylammonium bromide; CTAB) and cationic (sodium lauryl sulphate; SLS) surfactant-assisted hydrothermal method at different annealing temperatures (350 °C and 500 °C). The uniform surface morphology and crystallinity of the as-synthesized nanoflakes were analysed via field emission scanning electron microscopy, transmission electron microscopy, and powder X-ray diffraction techniques. Further, the electrochemical charge storage performances of these nanoflakes were explored in a three-electrode electrochemical measurement. The CTAB-assisted Co3 O4 showed an impressive charge storage performance in terms of higher specific capacitance (777.45 F g −1 ), energy (32.66 W h kg −1 ) and power (39.8 kW kg −1 ) densities ( E D and P D ) compared to that derived through SLS. Further, the CTAB-500 °C showed better cyclic durability with 83% retention of the initial capacitance after 5000 repeated cycles. Therefore, we presume that the present synthetic strategy will be a scalable and efficient method for the synthesis of Co3 O4 that can be used as a future energy storage material for sustainability.